Practical aspects of model predictive control in linear systems and cognitive maps - Mishchenko, M. (Проблеми керування та інформатики, 2023)
The paper discusses the application of the model predictive control (MPC) approach for stabilizing linear systems in discrete time. Although stabilization in linear systems has been well studied within control theory, the more recent model predictive control approach enables faster stabilization trajectories, albeit with a greater number of required computations. Due to significant progress in computing power since the inception of control theory, the practical implementation of model predictive control has become feasible. This approach yields significantly better results, but its application requires considerable attention, as incorrect use can lead to many non-obvious and undesirable effects. This article sequentially discusses, explains, and demonstrates these effects with examples. An analysis of their causes revealed the requirements for such a model predictive control algorithm, the fulfillment of which ensures the reliable functioning of the controller. У роботі розглянуто особливості застосування підходу керування за прогнозною моделлю (model predictive control — MPC) для стабілізації лінійних систем у дискретному часі. Хоча стабілізація у лінійних системах уже добре досліджена в рамках теорії керування, більш новий підхід керування за прогнозною моделлю дозволяє отримувати швидші траєкторії стабілізації, але при більшій кількості необхідних обчислень. Завдяки суттєвому прогресові в обчислювальній потужності комп’ютерів з часів появи теорії керування, з’явилася практична можливість реалізації керування за прогнозною моделлю. Цей підхід дозволяє досягти значно кращих результатів, проте його застосування потребує значної уваги, адже його некоректне використання призводить до безлічі неочевидних і небажаних ефектів. У даній статті почергово обговорено, пояснено і на прикладах продемонстровано ці ефекти. Аналіз їхніх причин дозволив виявити вимоги до такого алгоритму керування за прогнозною моделлю, виконання яких забезпечить надійне функціонування контролера.